The economic case for education*. Issue 1 (2nd January 2016) - Woessmann, Ludger
Abstract : The case for education can be made from many perspectives. This paper makes the case for education based on economic outcomes. Surveying the most recent empirical evidence, it shows the crucial role of education for individual and societal prosperity. Education is a leading determinant of economic growth, employment, and earnings in modern knowledge-based economies. Ignoring the economic dimension of education would endanger the prosperity of future generations, with widespread repercussions for poverty, social exclusion, and sustainability of social security systems. Policy-makers interested in advancing future prosperity should particularly focus on educational outcomes, rather than inputs or attainment.